Analisis Proteksi Merek Terdaftar oleh Direktorat Jenderal Kekayaan Intelektual dari Masalah Pelanggaran Merek - Jerica April; R. Rahaditya (Syntax Literate, 2023)
The formulation of this study; 1) What is the benchmark of determination used by the Directorate General of Intellectual Property to certify that a mark has a trademark in essence similar to a registered mark? The method used in this journal is descriptive-analytical with data collection through literature study. Descriptive-analytical research means a type of research that combines 2 elements contained in descriptive research and analytical research. The benchmark of the Directorate General of Intellectual Property in determining the similarity of a mark in essence with a registered mark is when the mark submitted for registration has similarities in principal or significant similarities with the mark that has been registered. This can include similarities in the main elements or essence of the brand such as similarities in shape, mode of placement, similarity of writing, and similarity of sound that can create potential confusion among consumers.